ANALISIS INTERVENSI SUAMI ATAS KEWARISAN DALAM PERSPEKTIF HUKUM ISLAM (STUDI KASUS DI GAMPONG PAYA RANGKULUH BIEREUEN) - M.Iqbal; Kana Rizki (Jurnal Syariah dan Ekonomi Islam, 2024)
This study generally aims to determine the factors underlying the rejection of inheritance, the consequences caused by the rejection of inheritance and the review of Islamic law on the rejection of inheritance analysis of husband's intervention in Gampong Paya Rangkuluh. The form of this research is carried out with a qualitative approach, meaning that the data that has been collected is classified into categories based on the similarity of the type of data. Based on the findings of this study, the factor of rejection of inheritance is caused by the husband's intervention factor, lack of inheritance knowledge and suspicion of other heirs and from the data studied the husband's influence is very fundamental to the rejection of property which causes consequences including the severance of friendship between the heirs, even among them no longer greet each other and do not visit each other, more ironically the husband of the heir who refused now hates his in-laws, some of the inheritance is neglected. Where the assets that can be utilized become useless without anyone to take care of them, even more feared is that one of the heirs can eat the assets of another heir without permission, and finally the heir who rejects the inheritance feels inconvenience (Inconvenience) because he is at a loss, in accepting or rejecting the inheritance. Therefore, by looking at the consequences that arise, the rejection of inheritance is not allowed and is forbidden by law.